Factors associated with dental attendance pattern among adults attending IIUM health facilities in Kuantan, Malaysia - Mohd, Farah Natashah; Said, Abdul Hadi; Mohd Ibrahim, Mohamad Shafiq; Abu Zarim, Khairunnisa; Ali, Aainaa; Maluin, Nur Afirah; A Rahaman, Nabila (Malaysian Dental Association (MDA), 2021)
Background: There is a lack of evidence about dental attendance patterns among adults in Malaysia. Most studies focused mainly on adolescents, school children and antenatal mothers. Aim: This research aims to assess the pattern of dental attendance among adults in Kuantan, Malaysia and its associated factors. Materials and methods: This were a cross sectional survey assessing the pattern of dental visits among adults attending IIUM Family Health Clinic and IIUM Medical Centre between February to December 2019 using adapted UK Adult Dental Health Survey 2009 questionnaires. We further examined the association between sociodemographic profile and the frequency of dental attendance using Chi-square test and Mann-Whitney test. Further analysis was done using simple logistic regression analysis to determine factors associated with a regular dental visit. Results: It is intriguing to know that two-third (68.5%) of the participants only came for dental visits when they have dental-related problems. Only 18% of the participants came for dental check-ups every six months. There were significant associations between age, gender and occupation with the frequency of dental visits with p<0.05. Older age and male group were less likely to come for a regular dental visit. Meanwhile, professionals workers and students were more likely to come for regular dental visits compared to those who were unemployed. Conclusion: Majority of adults in Kuantan only come for dental treatments when they have dental-related problems. Unemployed, older age and male participants were found to be irregular attendees while professionals workers and students were more likely to come for regular dental visits.